The Quantitative Analysis of Distortions in a Simple General Equilibrium Model - Pettengill, John (Review of Economic Studies, 1974)
Journal Article The Quantitative Analysis of Distortions in a Simple General Equilibrium Model Get access John Pettengill John Pettengill Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 1, January 1974, Pages 105–117, https://doi.org/10.2307/2296402 Published: 01 January 1974